Factors affect the vasectomy uptake of married couples in Bangka Belitung Islands, Indonesia - Dian Kristiani Irawaty; Yudi Rafani (Intelektual Pustaka Media Utama, 2021)
Vasectomy is a highly effective male contraception. However, the 2007 to 2017 Indonesia Demographic and Health Surveys reported no vasectomy cases in Bangka Belitung Islands. This study aimed to identify the number and its barriers to low vasectomy use in the Bangka Belitung Islands. The combination of qualitative and quantitative methods used in this study. This study utilized health clinics’ reports between 2015 and 2018 to identify whether or not vasectomy was executed in Bangka Belitung Islands. In-depth interviews were also carried out for medical practitioners, husbands, and wives to point out other crucial purposes of low vasectomy cases in the area. Vasectomy is regarded as a sexual displeasure contraceptive method. Those husbands had perceptions that vasectomy was similar to castration. They consider it as a sickening procedure. The wives perceived that vasectomy could make their husbands promiscuous. The misconceptions and stigma had been found as barriers for the low practice of vasectomy in the Islands. Reproductive health counseling for both husbands and wives need to be intensified to clarify those misconceptions about vasectomy. Vasectomy-specified campaign messages through various media channels should be conducted for couples in the area.